2023
DOI: 10.1038/s41588-022-01284-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-ancestry genome-wide analysis of atrial fibrillation unveils disease biology and enables cardioembolic risk prediction

Abstract: Atrial fibrillation (AF) is a common cardiac arrhythmia resulting in increased risk of stroke. Despite highly heritable etiology, our understanding of the genetic architecture of AF remains incomplete. Here we performed a genome-wide association study in the Japanese population comprising 9,826 cases among 150,272 individuals and identified East Asian-specific rare variants associated with AF. A cross-ancestry meta-analysis of >1 million individuals, including 77,690 cases, identified 35 new susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…Although rare damaging variants in cardiomyopathy genes may be investigated through targeted sequencing, evaluating risk attributable to common variants relies on PRS, which aggregates an individual's genetic risk for acquiring a phenotype over millions of common genetic variants. An inverse correlation between high PRS risk and age of atrial fibrillation onset has also been observed [2 ▪▪ ], as well as an association between high atrial fibrillation PRS risk in individuals without a diagnosis of atrial fibrillation and increased risk of cerebral infarction and cardioembolic stroke in a recent trans-ancestry GWAS [2 ▪▪ ]. Taken together, results from these studies suggest there may be utility in genetic testing to improve atrial fibrillation risk stratification and in identifying individuals at risk for early-onset atrial fibrillation in a subset of individuals.…”
Section: Advances In Atrial Fibrillation Genetics In the Clinicmentioning
confidence: 84%
See 4 more Smart Citations
“…Although rare damaging variants in cardiomyopathy genes may be investigated through targeted sequencing, evaluating risk attributable to common variants relies on PRS, which aggregates an individual's genetic risk for acquiring a phenotype over millions of common genetic variants. An inverse correlation between high PRS risk and age of atrial fibrillation onset has also been observed [2 ▪▪ ], as well as an association between high atrial fibrillation PRS risk in individuals without a diagnosis of atrial fibrillation and increased risk of cerebral infarction and cardioembolic stroke in a recent trans-ancestry GWAS [2 ▪▪ ]. Taken together, results from these studies suggest there may be utility in genetic testing to improve atrial fibrillation risk stratification and in identifying individuals at risk for early-onset atrial fibrillation in a subset of individuals.…”
Section: Advances In Atrial Fibrillation Genetics In the Clinicmentioning
confidence: 84%
“…Of these new atrial fibrillation variants, two (rs202030113 near SYNE1 and rs778479352 in FGF13 ) had not been reported outside of East Asian populations. In a trans-ancestry meta-analysis of an additional 77 690 individuals with atrial fibrillation across several European and Finnish atrial fibrillation cohorts, a total of 35 novel atrial fibrillation loci not previously reported at the genome-wide significance level were identified (Table 1) [2 ▪▪ ], illustrating the continued utility of GWAS across multiple diverse population ancestries in uncovering new genetic atrial fibrillation associations.…”
Section: Advances Linking Common Variants and Atrial Fibrillationmentioning
confidence: 91%
See 3 more Smart Citations